ANALYSIS OF THE DEVELOPMENT OF THE SKI TOURISM - A. Kondybayev; G.Uashov (Academic Journal of Physical and Chemical Sciences, 2019)
Tourism as an aggregated sector of economic development is a socially oriented innovation complex of directions that ensures the replenishment of the state budget, the growth of employment and self-employment of the population, the creation of conditions for the restoration of efficiency, maintenance and strengthening of people’s health in the maximum environmental safety regime. The tourism industry is one of the largest and fastest growing industries in the world. The global tourism industry forms 10% of world GDP and creates every 11th working position. Even in times of crisis, tourism gives an annual increase of about 4-5%. According to forecasts of the World Tourism Organization, by 2030, international tourism will grow by 3.3% per year and will reach 1.8 billion tourists. Ski tourism is a very important segment of today’s highly profitable domestic and foreign tourism market. The corresponding data indicate that about 2,000 ski resorts operating in about 80 countries around the world have about 6 million housing bed spaces for those who are engaged in winter sports. The article analyzed the distribution of ski resorts, ski visits at developed ski resorts, the number of international skiers who entered, also it contains the comparative analysis of the level of development of the ski industry in Central Asia, as well as an overview of the development of ski resorts.